2005
DOI: 10.1111/j.1365-3091.2005.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Zebra dolomitization as a result of focused fluid flow in the Rocky Mountains Fold and Thrust Belt, Canada

Abstract: Discordant zebra dolomite bodies occur locally in the Middle Cambrian Cathedral and Eldon Formations of the Main Ranges of the Canadian Rocky Mountains Fold and Thrust Belt. They are characterized by alternating dark grey (a) and white (b) bands, forming an ‘abba’ diagenetic cyclicity. These bands developed parallel to both bedding and cleavage. Dark grey (a) bands consist of fine (< 300 μm) non‐planar crystalline impure dolomite. The white (b) bands are composed of coarse (up to several millimetres) milky‐whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 73 publications
(140 reference statements)
6
73
1
3
Order By: Relevance
“…6a). This en echelon vein array geometry is consistent with a simple shear component of the deformation controlling vein development (Mazzoli and Di Bucci, 2003;Mazzoli et al, 2004, and references therein), a feature that has been frequently described in other zebra-dolomites (Wallace et al, 1994;Nielsen et al, 1998;Vandeginste et al, 2005;Diehl et al, 2010). Bedding-parallel simple shear may be related with flexural slip/flow folding, or be associated with the gliding of rock panels during thrusting.…”
Section: Field Observationsmentioning
confidence: 55%
See 1 more Smart Citation
“…6a). This en echelon vein array geometry is consistent with a simple shear component of the deformation controlling vein development (Mazzoli and Di Bucci, 2003;Mazzoli et al, 2004, and references therein), a feature that has been frequently described in other zebra-dolomites (Wallace et al, 1994;Nielsen et al, 1998;Vandeginste et al, 2005;Diehl et al, 2010). Bedding-parallel simple shear may be related with flexural slip/flow folding, or be associated with the gliding of rock panels during thrusting.…”
Section: Field Observationsmentioning
confidence: 55%
“…It is presently debated whether the large scale circulation of fluids is triggered by tectonic charge or by the hydraulic head induced by regional topography (Garven and Freeze, 1984;Oliver, 1986;Bethke and Marshak, 1990;Deming and Nunn, 1991;Ge and Garven, 1994;Morrow, 1998). Whatever the origin of the fluid-flow, the dolostone bodies are generally found in the undeformed foreland at the front of the fold and thrust belt and may be associated with deep-seated, sub-vertical normal faults (Taylor and Sibley, 1986;Hurley and Budros, 1990;Berger and Davies, 1999;Wendte et al, 2009;Lavoie and Chi, 2010;Shah et al, 2010), although several examples of dolomites formed within the fold and thrust belts itself also exist ( Qing and Mountjoy, 1994;Swennen et al, 2003;Vandeginste et al, 2005). This paper illustrates a case study of dolomitization of Triassic basinal limestones within a Neogene fold and thrust belt (southern Apennines, Italy).…”
Section: Introductionmentioning
confidence: 99%
“…Zebra dolomites are from a textural point of view built up by alternating layers of matrix dolomite and cement dolomite in an ABBA arrangement (Vandeginste et al, 2005). Pores are generally elongated and occur between two layers of cement dolomite (Fig.…”
Section: Petrophysical Analysesmentioning
confidence: 99%
“…During the replacement of the limestone by dolomite the fluid flow was focused in these high permeability zones leading to higher dissolution and dolomitization rates and the formation of layers. Studies carried out on zebra dolomites in Belgium, Spain and Canada concluded that the pattern evolved during fracturing due to tectonic stress [8,9] or hydrofracturing during the pulsed influx of dolomitizing brines [12,13,15]. The light coarse grained dolomite bands are interpreted as being at least partly void filling cements which precipitated into extensional fractures [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the formation of the structure consists of several phases of which the dark fine grained dolomite is the first one. This first phase represents the replacement of the initial limestone by dolomite [5][6][7][8][9][10][11][12][13][14][15]. What exactly triggers the development of the subsequent phases, which build up the coarse grained regions and FIGURE 1 | Examples of zebra textures at different scales.…”
Section: Introductionmentioning
confidence: 99%